Antitumor Activity of Methanolic Extract of Pisonia Aculeata Leaf - Shweta P. Ghode; B. Rajkapoor; T. Subbraju (International Journal of Phytomedicine, 2011)
In order to scientifically appraise some of the anecdotal, folkloric, ethno medical uses of Pisonia aculeata Linn. (Nyctaginaceae), the present study was undertaken to examine the antitumor activity of methanolic extract of Pisonia aculeata leaves extract on Ehrlich Ascites Carcinoma (EAC) in mice. Tumor was induced in mice by intraperitoneal injection of Ehrlich Ascites Carcinoma cells (1X10 6 cells/mouse). Methanolic extract of Pisonia aculeata (MPA) was administered to the experimental animals at the doses of 200 & 400 mg/kg/day, p.o. The antitumor effect of the extract was evaluated by using survival time, haematological parameters, increase in body weight, solid tumor volume and peritoneal cell count. Oral administration of MPA increased the survival time and inhibits the weight gain of the tumor bearing mice. After 14 days of inoculation, the extract also reduces the solid tumor volume developed by the EAC cells. The findings of this study indicate that the MPA possesses significant antitumor activity on dose dependent manner.